THE EFFECT OF INVESTMENT, REGIONAL ORIGINAL REVENUE (PAD), GENERAL ALLOCATION FUND (DAU), AND REGIONAL EXPENDITURE ON ECONOMIC GROWTH IN REGENCIES AND MUNICIPALITIES OF WEST PAPUA PROVINCE - Devi Rahel Christina Mustamu; Anak Agung Ketut Ayuningsasi (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
Economic growth is an important indicator of regional development influenced by economic and fiscal factors, including investment, Regional Original Revenue (PAD), General Allocation Fund (DAU), and regional expenditure. This study aims to analyze the effect of investment, PAD, DAU, and regional expenditure on the economic growth of regencies/cities in West Papua Province during 2019–2022, both simultaneously and partially. The study employed a quantitative approach using secondary data obtained from Statistics Indonesia, the Directorate General of Fiscal Balance, and the Ministry of Investment and Downstream Industry/BKPM. Data were analyzed using multiple linear regression with SPSS version 22 through descriptive statistical tests, classical assumption tests, F-test, t-test, and coefficient of determination. The results show that all variables simultaneously have a significant effect on economic growth. Partially, investment has no significant effect, while PAD and regional expenditure have a positive significant effect, and DAU has a negative significant effect. Regional expenditure is the most dominant variable, with a coefficient of determination of 87%.